Linking ethnic/racial discrimination to adolescent mental health: Sleep disturbances as an explanatory pathway. Issue 4 (2nd March 2022) - Yip, Tiffany; Xie, Mingjun; Cham, Heining; El Sheikh, Mona
Abstract: Ethnic/racial discrimination is associated with negative psychosocial outcomes, and this study considered sleep disturbance as a mediating pathway. Employing a combination of daily diary and biannual surveys, multilevel structural equation models estimated the indirect effects of sleep/wake concerns on negative, anxious, and positive mood, rumination, and somatic symptoms. In a sample of 350 urban Asian (74% Chinese, 8% Korean, 4% Indian, 1% Filipinx, 1% Vietnamese, and 12% other), Black, and Latinx (25% Dominican, 24% South American, 22% Mexican, 15% Puerto Rican, 5% Central American, and 9% other) youth ( M = 14.27 years, 69% female, 77% U.S. born, 76% monoethnic/racial, data collected from 2015 to 2018), there was evidence for sleep disturbances mediating the impact of ethnic/racial discrimination on adjustment. Nighttime disturbance, daytime dysfunction, and daytime sleepiness evidenced partial or full mediation for daily‐ and person‐level outcomes (υ = 0.1%–17.9%). Reciprocal associations between sleep disturbances and negative mood and rumination were also observed.